(untitled) (Journal of Hama University, 2025)
The research was carried out in an open field in Kafriya/ Lattakia Governorate, Syria, during the agricultural season 2023. The aim was to study the morphological characteristics, vegetative growth and productivity of four spinach varieties Spinacia oleracea L. introduced to Syria and traded among farmers, namely (Stwike, Matador, Esbolitsky, and Jernolitsky). The results showed that these varieties varied in most of the studied characteristics. The Stwike variety significantly outperformed the rest of the varieties in terms of the average green area, which reached 1700 cm2/plant, and the lowest leaf area reached 1200 cm2/plant for the Jernolitsky variety. This in turn was reflected in the plant weight and productivity. The Stwike variety significantly outperformed the rest of the varieties in terms of plant weight, which recorded 82 g, while it reached 74, 72, and 52 g for the Esbolitsky, Matador, and Jernolitsky varieties, respectively. The Stwike variety also was more significant than the rest of the varieties in terms of production quantity, as it recorded: 4.1, 3.6, 3.7, 2.6 kg/m2 for the varieties Stwike, Espolitsky, Matador and Jernolitsky, respectively.